(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Based on pre-revolutionary sources, specialized literature, and field ethnographic materials, this report analyzes the history of the settlement of ethnic Kyrgyz in the territory of Central Kazakhstan—Karkaraly, Aktogay, Shet, Nurinsky, and Kazybek districts of the Karaganda region, as well as Zhanaarka district of the Ulytau region. It is shown that this process had a dual and forced nature: 1) Initially, the studied Kyrgyz migrated to this region from Southern Siberia and Altai, starting from the late 16th century and continuing through the 17th-18th centuries, driven by oppression from the tsarist authorities and Dzungar invaders; 2) The next major and forced stage of migration coincided with the capture and hostage-taking of Kyrgyz in the 1750s-1770s by the Khan of the Middle Zhuz, Abylai. Subsequently, they, along with other representatives of fraternal Turkic peoples such as the Bashkir-Yesteki, Turkmen, Karakalpaks, and others, became sub-ethnic groups, joining various Kazakh tribal groups, including the Argyns. Despite their centuries-old history in Kazakhstan and incorporation into various clans, tribes, and subdivisions of the Kazakh ethnos, they did not forget their ethnic history and identified themselves as Kyrgyz.